Canada Since 1945 : Revised Edition - Bothwell, Robert; English, John, 1945-; Drummond, Ian M. (Book collections on Project MUSE., 2001)
From the preface: "A visitor seeing Canada for the first time since 1939 might well conclude that Canada, even more than nations devastated by war, has become another country. On the surface so much remains the same: the Liberals prevail in Ottawa; the provinces quarrel with Ottawa and among themselves; and we worry about Americans in our future. But most of the pieces have been rearranged, and the effect of the picture is quite different...This is a book about our own times, and as such it expresses definite views. No reader will agree with everything we say. We have not tried to end debate; we have tried to clarify and broaden. We trust that our readers will be encouraged to seek for themselves a better understanding of where Canadians have been and what they have become." Electronic Format Disclaimer: Images removed at the request of the rights holder.